Improvement of cyclodextrin glucanotranferase excretion and cell viability of recombinant Escherichia coli immobilized on hollow fiber membrane - Rohaida, Che Man (2016)
The excretion of a recombinant enzyme into culture medium presents significant advantages over cytoplasmic expression. However, cell lysis is one of the major drawbacks during the excretion of recombinant enzyme when using Escherichia coli (E. coli) as a host. Cell immobilization is a promising solution for the enhancement of enzyme excretion with reduction of cell lysis. In the present study, a recombinant E. coli was immobilized using hollow fiber membrane to improve the enzyme excretion, cell viability and plasmid stability. The effects of different polymers of hollow fiber membrane and culture conditions on the cyclodextrin glucanotransferase (CGTase) excretion, cell lysis and plasmid stability of immobilized E. coli were investigated. The immobilized cells on a polyvinylidene fluoride polymer exhibited a 2.0-4.5-fold increase in the CGTase excretion with 18-95% reduction of cell lysis and over 100% increment of plasmid stability compared to the free cells. The CGTase excretion was successfully optimized by response surface methodology. Under the optimized conditions [25 °C of post- induction temperature, 0.011 mM isopropyl β-D-1-thiogalactopyronoside and pH 8.8], the CGTase excretion was 3.8-fold higher with 80% reduction of cell lysis compared to the value before optimization process. The use of low tryptone concentration (5 g/1) reduced the occurrence of cell lysis (90% reduction) and increased the plasmid stability (86% increment) without significant change in CGTase excretion in comparison with initial tryptone concentration (20 g/1). This approach (5 g/1) produced an approximately two times higher CGTase excretion (compared with 20 g/1 during) recycle process. The membrane bioreactor also showed 2.5-fold increase in the CGTase excretion (473 x 103 U/ml) with 75% reduction of cell lysis compared to shake flask culture (190 x 103 U/ml of CGTase activity). Hence, the immobilization of E. coli on hollow fiber membrane proved to be valuable for the excretion of recombinant proteins in E. coli with high cell stability.